Contribution of Inventory Accounting Systems in Improving Inventory Internal Control - Ade Onny Siagian (Syntax Corporation Indonesia, 2020)
The purpose of this study was to determine the Role of Inventory Accounting Systems in Improving the Inventory Internal Control Structure at Putri Mayasari Cilandak. The research method used in this study is a qualitative research method with a case study approach and the data collected consists of primary and secondary data. Then Primary Data is collected through interviews, observations, and documentation, while Secondary Data is collected through library research to determine the role of the inventory accounting system in improving the structure of internal inventory control. The results of the study found that the role of the inventory accounting system in improving the internal control structure of inventory has been implemented properly and correctly. Keywords: Inventory, Accounting System, Internal Control